0011 Work Hard, Sleep Hard: Vigorous Workdays and Sleep Difficulties. (25th May 2022) - Jeppson, Jake; Mason, Brooke; Wills, Chloe; Tubbs, Andrew; Killgore, William; Grandner, Michael
Abstract: Introduction: It is common in America to work 5 or 6 days as a full work week. This is exhausting, especially for those with a vocation that requires vigorous physical activity during the work day. Sleep is an important factor when assessing workplace efficiency, as those able to obtain regular healthy sleep will perform better. Methods: A multinomial logistical regression analysis was conducted on the 2017 - March 2020 data collected from the National Health and Nutrition Examination Survey (NHANES) to explore a relationship between those with self-assessed sleep difficulties and the number of days of vigorous physical activity during work. The specific question used for analysis was, "Does your work involve vigorous-intensity activity that causes large increases in breathing or heart rate like carrying or lifting heavy loads, digging or construction work for at least 10 minutes continuously?" If yes, the number of days during a typical week was recorded. Sleep difficulties were self-reported as difficulties "falling asleep, staying asleep, or sleeping too much" within the previous two weeks, categorized as "never, " "less than half the days, " "more than half the days, " and "nearly every day." Reported results were unweighted; weighted results are forthcoming. Results were adjusted for sex, age, race/ethnicity, education level, and relationship status. Results: Compared to those with no days of vigorous physical activity at work, those with 2 days were more likely to report having sleep difficulties several days in the past 2 weeks (OR: 1.13, [1.00, 1.73], p=0.049). those reporting 6 days per week of vigorous work-related activity were less likely to report sleep difficulties several days (OR: 0.73, [0.59, 0.91], p=0.004), more than half the days (OR: 0.67, [0.48, 0.93], p=0.016), or nearly every day (OR: 0.68, [0.50, 0.94], p=0.018). Those who reported 6 days per week of vigorous work-related activity were less likely to report sleep difficulties several days (OR: 0.75, [0.51, 0.98], p=0.038) or more than half the days (OR: 0.57, [0.34, 0.96], p=0.035). Conclusion: It is possible that a physically demanding job has protective effects on sleep quality when compared to those that did not have any vigorous physical activity related to their profession. Support (If Any):